Politik Hukum Perlindungan Anak Di Indonesia (JURNAL HUKUM SEHASEN, 2017)
The child is a trust and a gift from God Almighty who inherent in dignity and dignity as a human being upheld and every child born should get his rights. Child Protection is an effort by the government to reform laws aimed at ensuring the fulfillment of children's rights in order to grow, develop and participate optimally, according to human dignity and protection and violence. Identification of issues raised in this study are: (1) What is the political regulation of child protection law in Indonesia ?, (2) How is the implementation of child protection politics politics in Indonesia ?, and (3) How is the policy that can be done by government in giving protection to children which will come?The approach method used in the preparation of this research is the normative juridical approach, with secondary data as the source. The results show that the political regulation of child protection law in Indonesia begins with the existence of the Convention on the Rights of the Child expressed in Indonesia since October 5, 1990, and then Law no. 3 of 1999 concerning Juvenile Court, Law Number 39 Year 1999 on Human Rights, Law Number 23 Year 2002 on Child Protection, Law no. 35 Year 2014, until the issuance of Law No. 1 Year 2016 on Child Protection. The implementation of child protection law politics in Indonesia is still far from expected, still lack of legal protection for children either as victim or as perpetrator of crime. Policies that can be taken by the government in providing child protection in the future with legal reform efforts in Indonesia, the development of diversion and restorative justice concepts in the implementation of the Indonesian criminal justice system, and law enforcement that embodies substantive justice.Keywords: Political Law, Child Protection, In Indonesia